2000
DOI: 10.1097/00007632-200006150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Individuals With Asymptomatic Disc Abnormalities in Magnetic Resonance Imaging

Abstract: Physical job characteristics and psychological aspects of work were more powerful than magnetic resonance imaging-identified disc abnormalities in predicting the need for low back pain-related medical consultation and the resultant work incapacity. However,the conclusions are still preliminary, and replication of the findings in larger and more representative study samples is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
86
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(97 citation statements)
references
References 28 publications
6
86
0
5
Order By: Relevance
“…(28). The scale has been successfully employed in previous research (29) and has been shown to predict indicators of low-back pain in initially asymptomatic persons (30).…”
Section: Methodsmentioning
confidence: 99%
“…(28). The scale has been successfully employed in previous research (29) and has been shown to predict indicators of low-back pain in initially asymptomatic persons (30).…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10][11][12] However, these articles have mainly assessed the influence of genetics or environmental variables on the progression of overall disk degeneration in individual subjects, without focusing on the possible association of sequential degeneration of individual disks with annular tears.…”
mentioning
confidence: 99%
“…The authors went further to state that given the high prevalence of these findings and of back pain, the discovery by MRI of bulges or protrusions in people with low back pain may frequently be coincidental. In another study 19 , which tracked the natural history of individuals with asymptomatic disc abnormalities in magnetic resonance imaging the authors stated that the high rate of lumbar disc alterations recently detected in asymptomatic individuals by magnetic resonance imaging demands reconsideration of a pathomorphology-based explanation of low back pain and sciatica. .…”
mentioning
confidence: 99%